Comparison of Predictive Validity of Alvarado Score and Appendicitis Inflammatory Response (AIR) Score, A Hospital Based Observational Study - Madasi, Venkaiah (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2016)
Introduction: Various new risk stratification scores have been proposed to accurately diagnose appendicitis. In the wake of limited number of comparative studies of these new scores, with the existing scores, the current study has compared the validity and reliability of Alvarado score and AIR score in diagnosis of appendicitis in a tertiary care teaching hospital. Materials & Methods: The current study was a prospective observational study. conducted in a tertiary acre teaching hospital in south India, between July 2015 to August 2016, for a 12-month period. A total of 297 eligible subjects were included. For each patient Alvarado score and AIR score were calculated and compared with histopathological evaluation. Results: The predictive validity of Alvarado score as assessed by area under the ROC curve was 0.74 (95% CI 0.62 to 0.85), as compared to 0.95 (95 % CI 0.92 to 0.98) for AIR score. The sensitivity of the AIR score was 95.7% as compared to 87.3% sensitivity of ALVARADO score. AIR score had s specify of 90.5%, as compared to 52.4% for Alvarado score. Correspondingly, both false positive (47.6% vs. 9.5%) and false negative (12.7% vs.4.3%) rates were higher for Alvarado score. The positive and negative predictive values of Alvarado score were 96% and 23.9%, as compared to 99.2% and 61.3% for AIR score. The overall diagnostic accuracy of Alvarado score was 85%, as compared to 95% for AIR score. Conclusions: The newly proposed appendicitis inflammatory response score had displayed a better validity and reliability, as compared to Alvarado score